A novel adaptive constant power optimal efficiency control strategy for bidirectional DS-LCC wireless charger - Yan, Jiabo; Aziz, Mohd Junaidi Abdul; Idris, Nik Rumzi Nik; Takrouri, Mohammad Al; Sutikno, Tole (International Journal of Power Electronics and Drive Systems (IJPEDS), 2026)
This paper presents a novel adaptive constant power optimal efficiency control (ACPOEC) strategy that enables efficient constant power (CP) charging in a double-sided inductor-capacitor-capacitor (DS-LCC) wireless charger. The proposed control strategy is built upon triple-phase-shift (TPS) modulation and employs a pre-computed lookup table derived from offline optimization to achieve CP charging with corresponding optimal efficiency. The CP charger with the proposed strategy can eliminate switch-controlled capacitors (SCCs) in the topology. The proposed strategy is validated through simulation studies, achieving an efficiency range of 90.72% to 92.46%, which is also competitive with other advanced CP wireless charging systems. Compared with existing state-of-the-art CP wireless charging techniques, the wireless CP charger with the proposed ACPOEC strategy features a simplified topology, bidirectional power transfer capability, and competitive efficiency performance.